Mass Balance of 14 Icelandic Glaciers, 1945–2017: Spatial Variations and Links With Climate - Belart, Joaquín M. C.; Magnússon, Eyjólfur; Berthier, Etienne; Gunnlaugsson, Ágúst Þ.; Pálsson, Finnur; Aðalgeirsdóttir, Guðfinna; Jóhannesson, Tómas; Thorsteinsson, Thorsteinn; Björnsson, Helgi (Frontiers in Earth Science, 2020)
To date, most mass balance studies in Iceland have concentrated on the three largest ice caps. This study turns the focus towards smaller Icelandic glaciers, presenting geodetic mass-balance estimates for 14 of them (total area 1010 km 2 in 2017) from 1945 to 2017, in decadal time spans. These glaciers, distributed over the country, are subject to different climatic forcing. The mass balance, derived from airborne and spaceborne stereo imagery and airborne lidar, is correlated with precipitation and air temperature by a first-order equation including a reference-surface correction term. This permits statistical modelling of annual mass balance, used to temporally homogenize the mass balance for a region-wide mass balance assessment for the periods 1945–1960, 1960–1980, 1980–1994, 1994–2004, 2004–2010 and 2010–2017. The 14 glaciers were close to equilibrium during 1960–1994, with an area-weighted mass balance of 0.07±0.07 m w.e. a −1. The most negative mass balance occurred in 1994–2010, accounting for –1.20±0.09 m w.e. a −1 , or 21.4±1.6 Gt (1.3±0.1 Gt a −1 ) of mass loss. Glaciers located along the south and west coasts show higher decadal mass-balance variability and static mass-balance sensitivities to summer temperature and winter precipitation, –2.21±0.25 m w.e. a −1 K −1 and 0.22±0.11 m w.e. a −1 (10%) −1 respectively, while glaciers located inland, north and northwest, have corresponding mass-balance sensitivities of –0.72±0.10 m w.e. a −1 K −1 and 0.13±0.07 m w.e. a −1 (10%) −1 . These patterns are likely due to the proximity to warm (south and west) versus cold (northwest) oceanic currents.